From the History of State Examinations in Higher Medical School - N. T. Eregina (Высшее образование в России)
The article discusses one of the episodes of the history of Yaroslavl State Medical University – a change in approaches to the final certification of graduates of medical faculties. The author dwells on how, over the course of seven decades, starting from wartime, the order of conducting state examinations, the list of exam disciplines submitted for final certification, the content of tickets, the form of state graduation exams, the requirements for the graduates of a higher medical school have changed. The content of the article is illustrated with photographic documents that clearly demonstrate the atmosphere of the exams of the past decades.